2020
DOI: 10.1111/nmo.13895
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ROCK signaling pathway accelerates enteric neural crest cell‐based therapy after transplantation in a rat hypoganglionic model

Abstract: Background Hirschsprung's disease (HSCR) is a congenital gastrointestinal disorder, characterized by enteric ganglia absence in part or entire of the colon, due to abnormal colonization and migration of enteric neural crest cells (ENCCs) during development. Currently, besides surgery which is the main therapy for HSCR, the potential of stem cell‐based transplantation was investigated as an alternative option. Although promising, it has limitations, including poor survival, differentiation, and migration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 57 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…The common DEMs in the two datasets (including 11 upregulated and 5 downregulated genes) (figure 5B) are detailed in table 2, which were significantly enriched in the GO/KEGG terms of Rho protein signal transduction, Ras protein signal transduction, IKappaB kinase (IKK)/nuclear factor kappa B (NF-κB), and cytokine-mediated signaling pathway (interferon-gamma, interleukin-5, interleukin-10, etc) (figure 5C). Various studies have shown that Rho/ROCK,37–39 RAS/MAPK,20 33 40 and IKK/NF-κB20 41 signaling played crucial roles in neurogenesis, which suggests the significant roles of the common DEMs in HSCR pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The common DEMs in the two datasets (including 11 upregulated and 5 downregulated genes) (figure 5B) are detailed in table 2, which were significantly enriched in the GO/KEGG terms of Rho protein signal transduction, Ras protein signal transduction, IKappaB kinase (IKK)/nuclear factor kappa B (NF-κB), and cytokine-mediated signaling pathway (interferon-gamma, interleukin-5, interleukin-10, etc) (figure 5C). Various studies have shown that Rho/ROCK,37–39 RAS/MAPK,20 33 40 and IKK/NF-κB20 41 signaling played crucial roles in neurogenesis, which suggests the significant roles of the common DEMs in HSCR pathogenesis.…”
Section: Resultsmentioning
confidence: 99%